(untitled) - Verhoef-Verhallen, Esther J. J.; Challacombe, Stephen (Lisse, The Netherlands, 2004)
This book is an introduction to many different breeds of cats with information on history, temperament, care, and physical characteristics.
Includes index.
Includes glossary.
9-12
Keywords: Cats; Encyclopedias